Administration is right? - Tenório, Fernando Guilherme (1990)
The author's intention is to discuss if the amassed knowledge instrumental to the study of rational action, as concerns the ends withing the organizations, has been a democratic mediator between the "thinking" and the "acting". He also endeavours, on the other hand, to enlarge the scope of questions put forward in this article Anomalia do fato administrativo, published by the RAP in this issue of april, 1989, in which is focused the apathy now showed by Administration, considered as an area of knowledge.